Idealization and Exile: Constructing Identity, Reconstructing Life - Piñeiro Domínguez, María Jesús (Madrygal. Revista de Estudios Gallegos, 2015)
Starting from several examples of the peninsular narrative from the postwar period, we will analyze the effects of a process carried out by many exiles to survive the forced migration: the transformation of hostile realities into imaginary ideals. Idealization disguises feelings, and it contributes to the construction of a new identity and to the reconstruction of a life dashed by war. But it also represents an escape where the exiles cannot find refuge.
Keywords: Exile; idealization; literature; identity; migrations